(x+6)(x-4)=-16

Simple and best practice solution for (x+6)(x-4)=-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+6)(x-4)=-16 equation:


Simplifying
(x + 6)(x + -4) = -16

Reorder the terms:
(6 + x)(x + -4) = -16

Reorder the terms:
(6 + x)(-4 + x) = -16

Multiply (6 + x) * (-4 + x)
(6(-4 + x) + x(-4 + x)) = -16
((-4 * 6 + x * 6) + x(-4 + x)) = -16
((-24 + 6x) + x(-4 + x)) = -16
(-24 + 6x + (-4 * x + x * x)) = -16
(-24 + 6x + (-4x + x2)) = -16

Combine like terms: 6x + -4x = 2x
(-24 + 2x + x2) = -16

Solving
-24 + 2x + x2 = -16

Solving for variable 'x'.

Reorder the terms:
-24 + 16 + 2x + x2 = -16 + 16

Combine like terms: -24 + 16 = -8
-8 + 2x + x2 = -16 + 16

Combine like terms: -16 + 16 = 0
-8 + 2x + x2 = 0

Factor a trinomial.
(-4 + -1x)(2 + -1x) = 0

Subproblem 1

Set the factor '(-4 + -1x)' equal to zero and attempt to solve: Simplifying -4 + -1x = 0 Solving -4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 0 + 4 -1x = 0 + 4 Combine like terms: 0 + 4 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4

Subproblem 2

Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2

Solution

x = {-4, 2}

See similar equations:

| 5v^2+32v+35=0 | | 2x(x-12)=40 | | 11x=180 | | x^3-5x-6=0 | | 5x^3-x^2-320x+64=0 | | 6x-45=538 | | a+6-6a=12+3a | | X=8-6y | | 7x+5y=-18 | | (4u+1)(8-u)=u | | t^2-11t+30=0 | | 3(-4x+1)=27 | | x=.85x+.45(80-x) | | t^2-4t+4=0 | | 3+3+3+3+3=10 | | -5x+40=160 | | 5t+2=9t-2 | | 4(5x-7)=-56 | | 12b=18 | | 2(x-9)=-5x-46 | | 6(3z-1)-4(z+3)=3(z+1) | | 7+4w=-5 | | 2ln(7x)=-4 | | 3x-5=2x-3 | | .54-.07y=.2y | | 5y+4(y-7)=3(y+2)-5 | | 1.25*137= | | 5X+30=10(X*X) | | .75*137= | | 5s^2-8s=0 | | .25x-.125x=3-.0625x | | 4x+2(4y-3)=3 |

Equations solver categories